PELATIHAN MENULIS KARYA FIKSI UNTUK MENINGKATKAN KEMAMPUAN JURNALISME SASTRAWI - Misnan Misnan; Prisila Damayanty (Jurnal Pengabdian Teratai, 2021)
The purpose of the activity is to improve the literary journalism skills of students, through creative writing. This ability is dominantly needed, because it relates to the competence of da'wah communication in the demands of adaptability of using new media. The implementation method is carried out by training in writing literary works and lectures on various developments of literary journalism. Through this activity, the students gain technical insight and how to develop creative ideas to be developed in verbal communication and nonverbal communication. Verbal communication is by writing and preaching, while non-verbal communication is in forming the character of students who are multitasking as adaptive resources, who are highly competent in socio-religious and using new media technology